"Whom should We Help First?" Transnational Helping Practices in Ecuadorian Migration. (15th January 2010) - Boccagni, Paolo
Abstract Collective remittances, in the framework of migrant transnationalism, have been recently dealt with in some empirical research, especially on the Mexican‐US migration system. Far less studied is their significance in different migration flows, including their real contribution – as desirable as this may be – to local development. The article is concerned with a bottom up analysis of a migration flow where collective remittances – as the only way for emigrants to keep helping their local communities, well beyond their own families – are still in their infancy. It explores, through a translocal ethnography of Ecuadorian migration to Italy, the underlying attitudes, personal meanings and expectations – as well as the structural opportunities and constraints – accounting for helping practices at a distance. Charitable transfers to communities of origin are reconstructed as to their motivations, their main aims and beneficiaries, their embeddedness in mutual networks among immigrant co‐nationals. How is it that some of them decide to help "people in need" in their own communities overseas, or in their home towns, or in both? Is this an expression of communal belonging, or a matter of social status maintenance, or something else? Further reflections on the dilemmas inherent in transnational helping practices are then developed. Concluding remarks emphasize the relatively poor scope for such initiatives, in a recent and first‐generation flow over a long distance. While co‐ethnic solidarity overseas is a precondition for transnational helping practices, the latter are also affected by the developments of public policies in the countries of origin and of destination. Overall, an effective integration overseas is necessary for collective remittances to have some currency and impact.